Prospects in Tourism Marketing: A Study with Reference to Kerala as Tourism Destination - B. Udaya Bhaskara Ganesh and P. Jagadeesh (Bonfring, 2013)
ference to Kerala as Tourism Destination B. Udaya Bhaskara Ganesh and P. Jagadeesh Abstract--- Tourism has become a popular global leisure activity. Tourism is important, and in some cases, vital for many countries. It was recognized in the Manila Declaration on World Tourism of 1980 as "an activity essential to the life of nations because of its direct effects on the social, cultural, educational, and economic sectors of national societies and on their international relations." Tourism is a growing service industry which earns a substantial foreign exchange in many parts of the world. In India, kerala is the most important destination for the international tourists with its unique and enchanting land abounding in scenic beauty, rich in flora and fauna. To make the tourism a great success one has to take advantage of the modern technology to full extent. Many countries are promoting tourism and it has become a source of major income for countries like India, Singapore and Malaysia. Tourism is, of course, big industry in most developed countries like the US, the UK, France and Switzerland. Tourism industry is one in which there is high competition. The tourism should not only concentrate on promoting and selling packages for foreign tourist but should also induce domestic tourists to use the services. The price of the tourist package is the main criteria for people in India to consider making a trip. Tourists can be divided based on their socio- economical status, geographic differences, demographics and psychographics. The marketing mix elements of tourism industry help in creating an image of the tourist destination, building awareness of the services. Tourism is a service sector which earns a substantial foreign exchange to developing countries. In India, Kerala is one of the important destination for the international tourists with its unique nature beauty with backwaters, mountains and beaches. Kerala is often referred to as ‘God’s own country’, because of its extraordinary natural beauty resembling the heaven. Present paper is an attempt to market tourism by adapting the service marketing approach for achieving great success. This paper discusses services marketing mix concepts, its application in promoting kerala tourism and the strengths and problems of tourism in kerala.